2007
DOI: 10.1093/cvr/cvm079
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomeric dysfunction in heart failure

Abstract: Sarcomeric dysfunction plays a central role in reduced cardiac pump function in heart failure. This review focuses on the alterations in sarcomeric proteins in diseased myocardium that range from altered isoform expression to post-translational protein changes such as proteolysis and phosphorylation. Recent studies in animal models of heart failure and human failing myocardium converge and indicate that sarcomeric dysfunction, including altered maximum force development, Ca(2+) sensitivity, and increased passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
130
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 95 publications
11
130
2
1
Order By: Relevance
“…Excess production of reactive oxygen species (ROS) has been implicated in progression of chronic heart failure as well as in other cardiovascular disorders including ischemia-reperfusion injury and cardiovascular complications of hemolytic diseases [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Excess production of reactive oxygen species (ROS) has been implicated in progression of chronic heart failure as well as in other cardiovascular disorders including ischemia-reperfusion injury and cardiovascular complications of hemolytic diseases [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in experimental heart failure in the rat, we found a depression in myofilament function that was causally linked to alterations in Tn; a follow-up study demonstrated that this was due to, most likely, up-regulation of PKC-α activity and the subsequent phosphorylation of cardiac contractile proteins [5,6]. Likewise, studies by van der Velden et al indicate that depressed myofilament function in human heart failure is associated with alterations in Tn phosphorylation, as well as other contractile proteins such as myosin light chain and myosin-binding protein C [27]. Thus, maladaptive contractile protein function, and in particular contractile protein phosphorylation, may be a worthy signaling mechanism to target so as to restore contractile function of the ventricular myocyte in end-stage CHF.…”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…Although it is well recognized that disturbances in calcium regulation constitute an important mechanism in this process [7], it is now clear that heart failure is also associated with a decline in myofilament response to activator Ca 2+ [15,16,27,37,67,72]. Although isoform distribution and proteolytic cleavage of contractile proteins may play a role, (inappropriate) contractile protein phosphorylation has emerged as an important determinant of depressed myofilament function in various etiologies of heart failure [5,6,27,67]. For example, in experimental heart failure in the rat, we found a depression in myofilament function that was causally linked to alterations in Tn; a follow-up study demonstrated that this was due to, most likely, up-regulation of PKC-α activity and the subsequent phosphorylation of cardiac contractile proteins [5,6].…”
Section: Cardiac Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…PKA mediated phosphorylation of titin results in decreased stiffness of the cardiac myofilament. This process may be physiologically significant as it was recently shown that myocytes obtained from patients with diastolic heart failure were less compliant than normal cells and treatment of the skinned myocytes with PKA reversed this abnormality [10].…”
mentioning
confidence: 99%